Implementation of the Mind Mapping Model to Improve Students' Writing Creativity in Indonesian Language Learning at SMP Negeri 1 Panga - Munawarah; Yalis, Irma (MANDAILING GLOBAL EDUKASIA, 2025)
This study explores the effectiveness of the Mind Mapping learning model in enhancing the creativity of ninth-grade students in writing Indonesian language essays at SMP Negeri 1 Panga. Writing is a critical skill that reflects students’ ability to organize ideas, express opinions, and communicate effectively. However, many students face difficulties in generating ideas, structuring essays, and developing originality, which hinders their writing creativity. The research employed a Classroom Action Research (CAR) design, conducted over two cycles consisting of planning, acting, observing, and reflecting stages. Participants included 32 ninth-grade students aged 14–15 years. Data were collected through essay assessments, observation of student engagement, and documentation of classroom activities. Quantitative data were analyzed using descriptive statistics, while qualitative data provided insights into students’ creativity, idea generation, and writing processes. Findings indicate significant improvement in students’ writing creativity after implementing the Mind Mapping model. The percentage of students meeting the creativity criteria increased from 40% in the preliminary assessment to 87% in the second cycle. Observations revealed enhanced idea organization, originality, and engagement in writing tasks. The study concludes that the Mind Mapping model is an effective instructional strategy for fostering writing creativity in Indonesian language classes, supporting students’ cognitive, organizational, and creative development.